Novel analytical approaches for studying degradation in polypropylene and propylene-1-pentene copolymers - De Goede, Stefan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.